Direct observation of kink evolution due to Hund’s coupling on approach to metal-insulator transition in NiS2−x Se x - Bo Gyu Jang (Nature Portfolio, 2021)
A decisive spectroscopic evidence of the Hund’s coupling energy scale in multi-orbital correlated systems has been lacking. Here, the authors identify a kink feature due to Hund´s coupling in the spectral function of NiS2x Se x as they track its evolution across the Mott-insulator transition.